2015
DOI: 10.3892/ijo.2015.3052
|View full text |Cite
|
Sign up to set email alerts
|

The phosphatidylinositol 3-kinase/Akt and c-Jun N-terminal kinase signaling in cancer: Alliance or contradiction? (Review)

Abstract: Abstract. The phosphatidylinositol 3-kinase (PI3K)/Akt signaling pathway and c-Jun N-terminal kinase (JNK) pathway are responsible for regulating a variety of cellular processes including cell growth, migration, invasion and apoptosis. These two pathways are essential to the development and progression of tumors. The dual roles of JNK signaling in apoptosis and tumor development determine the different interactions between the PI3K/Akt and JNK pathways. Activation of PI3K/ Akt signaling can inhibit stress-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 92 publications
5
65
0
Order By: Relevance
“…Studies have shown that specific anti-sense oligonucleotides against JNK lead to decreased cell growth by promoting apoptosis in gastric, lung and prostate cancer cells (104, 105). On the other hand, the observed decrease in proliferation of TRPM2 KD cells could be due to a decrease in p-AKT (106,107); crosstalk between JNK and AKT signalling pathways has been established and shown to inhibit apoptosis as a means of promoting cancer cell survival (108). Altogether, our study provides new evidence that TRPM2 triggers both, the AKT and JNK signalling pathways to promote gastric cancer cell survival.…”
Section: Discussionsupporting
confidence: 49%
“…Studies have shown that specific anti-sense oligonucleotides against JNK lead to decreased cell growth by promoting apoptosis in gastric, lung and prostate cancer cells (104, 105). On the other hand, the observed decrease in proliferation of TRPM2 KD cells could be due to a decrease in p-AKT (106,107); crosstalk between JNK and AKT signalling pathways has been established and shown to inhibit apoptosis as a means of promoting cancer cell survival (108). Altogether, our study provides new evidence that TRPM2 triggers both, the AKT and JNK signalling pathways to promote gastric cancer cell survival.…”
Section: Discussionsupporting
confidence: 49%
“…Stress activated protein kinases, such as JNK and p38, are activated by various stress stimuli. 33 Bioactive compounds are known to induce apoptosis by activating JNK and p38. Consistent with these results, we observed that JNK and p38 activation was involved in ω-HUA-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of NVP-BEZ235 and MEK1/2 inhibitors UO126 or SL327 displays synergistic inhibitory effect on self-renewal and tumorigenic capacities of GBM stem-like cells (GSLCs), and prolongs the survival of mice with GSLC xenograft [96]. In addition, PI3K/Akt and MKK4/JNK pathways also co-operate to regulate cancer cell survival, migration and invasion [117]. Our previous study showed that concurrent inhibition of PI3Kβ and JNK synergistically suppresses GBM cell proliferation and migration, and tumor growth in U-87 MG xenograft mice [19].…”
Section: Introductionmentioning
confidence: 99%